A new exTTF-crown ether platform to associate fullerenes: Cooperative n-π and π-π Effects - Grimm, Bruno; Santos, Jose; Illescas, Beatriz M.; Munoz, Antonio; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2010)
A new and readily available exTTF-bis(crown ether), 1, efficiently recognizes C as well as C by means of cooperative π-π and n-π interactions. The geometrical (concave-convex) and electronic (donor-acceptor) complementarity accounts on one hand for remarkable binding strengths, with association constants reaching 10 M in benzonitrile, and on the other hand for lifetimes of the photogenerated radical ion pair state on the order of 45 ps. © 2010 American Chemical Society.

Balancing binding strength and charge transfer lifetime in supramolecular associates of fullerenes - Grimm, Bruno; Isla, Helena; Perez, Emilio M.; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2011)
A macrocyclic exTTF host for fullerenes offers control over the electronic coupling between an electron donor and an acceptor, and stabilizes the charge separated state lifetimes into the range of 500 ps. © 2011 The Royal Society of Chemistry.

Bowl-shape electron donors with absorptions in the visible range of the solar spectrum and their supramolecular assemblies with C 60 - Isla, Helena; Grimm, Bruno; Perez, Emilio M.; Rosario Torres, M.; Angeles Herranz, M.; Viruela, Rafael; Arago, Juan; Orti, Enrique; Guldi, Dirk Michael; Martin, Nazario (Chemical Science, 2012)
We describe the synthesis, electronic, optical and photophysical properties of a family of three electron-donor bowl-shaped organic molecules that absorb light in the whole range of the visible spectrum (up to 800 nm in one case), and associate C in solution with binding constants in the range of 10 -10 M as measured from both UV-vis and fluorescence titrations in several solvents. These molecules are π-extended derivatives of tetrathiafulvalene, based on a truxene core to which two or three units of dithiole are covalently attached. The inclusion of the bulky dithiole groups is responsible for their bowl-shape geometry, which allows them to associate with C , and their electron-donor character. The symmetric derivative 1, with three dithiole units, absorbs light in the 370-520 nm range. Exchanging one of the dithiole groups by an electron-withdrawing group, ketone (2) and dicyanomethylene (3), results in an intramolecular push-pull effect that extends the absorption to nearly 700 nm in the case of 2, and up to 800 nm in the case of 3. Transient absorption measurements, supported by spectroelectrochemical and radiolytical experiments, reveal that upon photoexcitation of the 1C associate the fully charge-separated state 1 C is generated, with lifetimes of hundreds of picoseconds. Molecular-level understanding of the electronic and supramolecular properties of 1-3 is provided by density functional theory calculations. © 2012 The Royal Society of Chemistry.

Charge transfer in sapphyrin-fullerene hybrids employing dendritic ensembles - Grimm, Bruno; Karnas, Elizabeth; Brettreich, Michael; Ohta, Kiminori; Hirsch, Andreas; Guldi, Dirk Michael; Torres, Tomas; Sessler, Jonathan L. (Journal of Physical Chemistry B, 2010)
A new approach to creating noncovalent charge transfer ensembles is described. It is based on two components that are linked through anion-receptor interactions. The first component is sapphyrin, a pentapyrrolic expanded porphyrin, which is capable of carboxylate anion recognition and more importantly can act as a photodonor when irradiated in the presence of a suitable electron acceptor. The second component is the electron acceptor and consists of one of two different C fullerene cores functionalized with multiple carboxylate anion groups arranged in a dendritic fashion. Depending on the specific choice of the fullerene carboxylate anion dendrimer employed in ensemble construction, 1:1 or 1:2 complexes are formed when the C cores are titrated with sapphyrin. The resulting noncovalent arrays undergo sapphyrin-to-fullerene electron transfer when irradiated with 387 nm light. This gives rise to charge separated states with lifetimes of ca. 470 and 600 ps in the case of the 1:1 and 1:2 sapphyrin-fullerene ensembles, respectively. © 2010 American Chemical Society.

Enhanced binding strengths of acyclic porphyrin hosts with endohedral metallofullerenes - Grimm, Bruno; Schornbaum, Julia; Cardona, Claudia M.; Van Paauwe, John D.; Boyd, Peter D. W.; Guldi, Dirk Michael (Chemical Science, 2011)
The complementary use of spectroscopy and electrochemistry shed light onto the supramolecular interactions of calixarene scaffold bearing bisporphyrins 1 and 2 as hosts with a series of fullerenes -C , Sc N@C , and Lu N@C - as guest molecules. Importantly, the present work shows a noticeable variation in binding strength when C or endohedral fullerene guests are included into the bisporphyrins hosts. These sizeable differences could be clarified by computational models of the host-guest complexes, on the one hand, and a systematic investigation of the electron transfer chemistry, on the other hand. Detailed studies document an oxidative charge transfer (i.e., electron transfer from the bisporphyrin to the fullerene) for the C inclusion complexes, while a reductive charge transfer (i.e., electron transfer from the fullerene to porphyrin) is operative in the endohedral metallofullerene host-guest complexes. © The Royal Society of Chemistry 2011.

Enhancing molecular recognition in electron donor-acceptor hybrids via cooperativity - Krick Calderon, Rafael; Valero, Julian; Grimm, Bruno; De Mendoza, Javier; Guldi, Dirk Michael (Journal of the American Chemical Society, 2014)
Herein, we report the synthesis of guanidinium bis-porphyrin tweezers 1 and fullerene carboxylate 3, their assembly into a novel supramolecular 1@3 electron donor-acceptor hybrid, and its characterization. In solution, the binding constant affording 1@3 is exceptionally high. 1@3, which features a highly confined topography, builds up from a combination of guanidinium- carboxylate hydrogen bonding and π-π stacking/charge-transfer motifs. The latter is governed by interactions between the electron-donating porphyrin and the electron-accepting fullerene. Importantly, positive cooperativity between the applied binding motifs is corroborated by a number of experimental techniques, such as NMR, absorption, fluorescence, etc. In addition, transient absorption experiments shed light onto electron-transfer processes taking place in the ground state and upon photoexcitation. In fact, porphyrin excitation powers an electron transfer to the fullerene yielding charge separated state lifetimes in the nanosecond regime. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-07

Pairing fullerenes and porphyrins: Supramolecular wires that exhibit charge transfer activity - Wessendorf, Florian; Grimm, Bruno; Guldi, Dirk Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2010)
A concept is elaborated of pairing electron donors and electron acceptors that share a common trait, wire-like features, as a powerful means to realize a new and versatile class of electron donor-acceptor nanohybrids. Important variables are fine-tuning (i) the complexation strength, (ii) the electron/energy transfer behavior, and (iii) the solubilities of the resulting architectures. In particular, a series of supramolecular porphyrin/fullerene hybrids assembled by the hydrogen bonding of Hamilton receptor/cyanuric acid motif has been realized. Putting the aforementioned variables into action, the association constants (K), as they were determined from H NMR and steady-state fluorescence assays, were successfully tweaked with values in the range of 10-10 M . In fact, our detailed studies corroborate that the latter reveal a dependence on the nature of the spacer, that is, p-phenylene-ethynylene, p-phenylene-vinylene, p-ethynylene, and fluorene, as well as on the length of the spacer. Complementary performed transient absorption studies confirm that electron transfer is indeed the modus operandi in our novel class of electron donor-acceptor nanohybrids, while energy transfer plays, if any, only a minor role. The accordingly formed electron transfer products, that is, one-electron oxidized porphyrins and one-electron reduced fullerenes, are long-lived with lifetimes that reach well into the time domain of tens of nanoseconds. Finally, we have used the distance dependence on electron transfer, charge separation and charge recombination, to determine for the first time a ß value (0.11) for hydrogen-bonding-mediated electron transfer. © 2010 American Chemical Society.

Powering reductive charge shift reactions - Linking fullerenes of different electron acceptor strength to secure an energy gradient - Villegas, Carmen; Luis Delgado, Juan; Bouit, Pierre-Antoine; Grimm, Bruno; Seitz, Wolfgang; Martin, Nazario; Guldi, Dirk Michael (Chemical Science, 2011)
We report here on one of the rare cases that realizes a reductive charge shift from a primary electron acceptor (C ) to a secondary electron acceptor (C ) in a ZnP-C -C conjugate. Initially, charge separation evolves from an excited state electron donor (ZnP). By far the most far reaching benefit from such a reductive pathway is a marked slow down of the energy wasting charge recombination when compared to the ZnP-C conjugate (i.e., picoseconds versus nanoseconds). © The Royal Society of Chemistry 2011.

Self-assembling depsipeptide dendrimers and dendritic fullerenes with new cis- and trans-symmetric Hamilton receptor functionalized zn-porphyrins: Synthesis, photophysical properties and cooperativity phenomena - Maurer, Katja; Grimm, Bruno; Wessendorf, Florian; Hartnagel, Kristine; Guldi, Dirk Michael; Hirsch, Andreas (European Journal of Organic Chemistry, 2010)
Two novel supramolecular building blocks, namely cis- and trans-symmetric zinc-porphyrins bearing Hamilton receptors as their focal points (10 and 15), were self-assembled with (i) first-, second- and third-generation depsipeptide cyanurates (21-23); (ii) second-generation dendrofullerene (24), and (iii) cyanuric acid substituted fullerene (20), and probed in a series of photophysical investigations. Importantly, an overall 1:2 stoichiometry was confirmed with binding con-stants Kn, and Hill coefficients nH that indicate remarkable cooperativities. As a general feature, stronger binding evolves from the trans-symmetric porphyrin isomer, although the increased steric demand of the depsipeptide ligands means that the binding constants decrease with each generation. The self-assembly of 10 or 15 with 20 affords novel electron donor-acceptor hybrids that reveal, upon excitation, intra-hybrid charge-transfer events. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Self-assembly, host-guest chemistry, and photophysical properties of subphthalocyanine-based metallosupramolecular capsules - Sanchez-Molina, Irene; Grimm, Bruno; Krick Calderon, Rafael; Claessens, Christian G.; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2013)
Four new subphthalocyanine-based capsules have been synthesized and characterized. These supramolecular systems have been successfully employed for the encapsulation of fullerenes and probed by a wide range of characterization methods, including NMR, UV-vis and fluorescence spectroscopy, electrospray ionization mass spectrometry, and electrochemistry. Furthermore, the binding constants of the host guest complexes were estimated. Finally, the photophysical properties revealed that the subphthalocyanines undergo a transduction of singlet excited-state energy to the fullerene inside the cavity upon photoexcitation. © 2013 American Chemical Society.

Step-by-step self-assembled hybrids that feature control over energy and charge transfer - Grimm, Bruno; Schornbaum, Julia; Jasch, Hannelore; Trukhina, Olga; Wessendorf, Florian; Hirsch, Andreas; Torres, Tomas; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2012)
In the current work, we have documented the use of two complementary supramolecular motifs, namely multipoint hydrogen bonding and metal complexation, as a means to control the step-by- step assembly of a panchromatically absorbing and highly versatile solar energy conversion system. On one hand, two different perylenediimides (1a/1b) have been integrated together with a metalloporphyrin (2) by means of the Hamilton receptor/cyanuric acid hydrogen bonding motif into energy transduction systems 1a•2 or 1b•2. Steady-state and time-resolved measurements corroborated that upon selective photoexcitation of the perylenediimides (1a/1b), an energy transfer evolved from the singlet excited state of the perylenediimides (1a/1b) to that of the metalloporphyrin (2). On the other hand, fullerene (3) and metalloporphyrin (2) form the electron donor-acceptor system 2•3 via axial complexation. Photophysical measurements confirm that an electron transfer prevails from the singlet excited state of 2 to the elec-tron- accepting 3. The correspondingly formed radical ion pair state decays with a lifetime of 1.0 ± 0.1 ns. As a complement to the aforementioned, the energy transduction features of 1a•2 were combined with the electron donor-acceptor characteristics of 2•3 to afford 1a•2•3. To this end, time-resolved measurements reveal that the initially occurring energy-transfer interaction (53 ± 3 ps) between 1a/1b and 2 is followed by an electron transfer (12 ± 1 ps) from 2 to 3. From multiwavelength analyses, the lifetime of the radical ion pair state in 1a•2•3 - as a product of a cascade of light-induced energy and electron transfer - was derived as 3.8 ± 0.2 ns.

Synthesis and photophysical properties of a hydrogen-bonded phthalocyanine-perylenediimide assembly - Seitz, Wolfgang; Jimenez, Angel J.; Carbonell, Esther; Grimm, Bruno; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Communications, 2010)
A supramolecular phthalocyanine-perylenediimide donor-acceptor array has been assembled by using a melamine/perylenediimide motif. Photoexcitation of the perylenediimide component affords transduction of singlet excited state energy to the energetically lower lying phthalocyanine. © 2010 The Royal Society of Chemistry.

Synthesis, characterization, and photoinduced energy and electron transfer in a supramolecular tetrakis (ruthenium(II) phthalocyanine) perylenediimide pentad - Jimenez, Angel J.; Grimm, Bruno; Gunderson, Victoria L.; Vagnini, Michael T.; Krick Calderon, Sandra; Salome Rodriguez-Morgade, M.; Wasielewski, Michael R.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2011)
Metal coordination was probed as a versatile approach for designing a novel electron donor/acceptor hybrid [PDIpy Ru(CO)Pc ] (1), in which four pyridines placed at the bay region of a perylenediimides (PDIpy ) coordinate with four ruthenium phthalocyanine units [Ru(CO)Pc]. This structural motif was expected to promote strong electronic coupling between the electron donors and the electron acceptor, a hypothesis that was confirmed in a full-fledged physicochemical investigation focusing on the ground and excited state reactivities. As far as the ground state is concerned, absorption and electrochemical assays indeed reveal a notable redistribution of electron density, that is, from the electron-donating [Ru(CO)Pc] to the electron-accepting PDIpy . The most important thing to note in this context is that both the [Ru(CO)Pc] oxidation and the PDIpy reduction are rendered more difficult in 1 than in the individual building blocks. Likewise, in the excited state, strong electronic communication is the inception for a rapid charge-transfer process in photoexcited 1. Regardless of exciting [Ru(CO)Pc] or PDIpy , spectral characteristics of the [RuPc] radical cation (broad absorptive features from 425 to 600 nm with a maximum at 575 nm, as well as a band centered at 725 nm) and of the PDI radical anion (780 nm maximum) emerge. The correspondingly formed radical ion pair state lasts for up to several hundred picoseconds in toluene, for example. On the other hand, employing more polar solvents, such as dichloromethane, destabilizes the radical ion pair state. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Trapping fullerenes with jellyfish-like subphthalocyanines - Sanchez-Molina, Irene; Claessens, C. G.; Grimm, Bruno; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2013)
Six electronically different concave-shaped subphthalocyanines (SubPcs) have been prepared for testing the structural factors governing fullerenes encapsulation. Thus, the supramolecular interaction of SubPcs with C and C fullerenes in solution has been studied by Job's plot and titration experiments, which yielded quantitative information on both the stoichiometry and strength of the complexes in toluene solution. The importance of the electronic nature of the SubPc was demonstrated, as it influences not only the stability of the complex, but also its stoichiometry. Alkyl chains incorporated in hexaalkylthio-substituted SubPcs seem to in some way cooperate in the binding process and influence its kinetics. In the resulting 2:1 complexes, the large absorption cross section of SubPcs throughout the visible part of the spectrum is the beginning of an unidirectional energy transfer to funnel the excited state energy from the periphery (i.e., two SubPcs) to the core (i.e., C and C). © 2013 The Royal Society of Chemistry.